2021
DOI: 10.3332/ecancer.2021.1245
|View full text |Cite
|
Sign up to set email alerts
|

CDK 4/6 inhibitor induced lung injury: a case report and review of literature

Abstract: Palbociclib is a cyclin dependent kinase (CDK) 4/6 inhibitor that is indicated in combination with an aromatase inhibitor for first-line treatment of hormone receptor-positive, human epidermal growth factor receptor 2 -negative advanced or metastatic breast cancer. The commonly described side effects of palbociclib are neutropenia, anaemia, thrombocytopenia, fatigue, nausea, stomatitis, alopecia, diarrhoea, decreased appetite, vomiting, asthenia, peripheral neuropathy and epistaxis. However, post approval, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Still, it did not improve lung function and led to the accumulation of in ammatory factors (including macrophages and T cells) in the lung 39 . The same phenomenon has been observed in clinical cases 40,41 . In the event of pneumonia that is suspected to be due to palbociclib, palbociclib should be discontinued, and glucocorticoids and oxygen therapy should be used as appropriate 41 .…”
Section: Discussionsupporting
confidence: 84%
“…Still, it did not improve lung function and led to the accumulation of in ammatory factors (including macrophages and T cells) in the lung 39 . The same phenomenon has been observed in clinical cases 40,41 . In the event of pneumonia that is suspected to be due to palbociclib, palbociclib should be discontinued, and glucocorticoids and oxygen therapy should be used as appropriate 41 .…”
Section: Discussionsupporting
confidence: 84%
“…related to these agents have been reported, indicating a potential association between CDK4/6 inhibitors and ILD/pneumonitis [48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study suggested that palbociclib augmented inflammatory cell recruitment (including macrophages and T cells) in the bronchoalveolar lavage fluid, which could be a consequence of the palbociclib-induced cell cycle arrest with relevant cellular senescence [44,61]. It was further proposed that in the presence of cell cycle inhibitor like palbociclib, the inflammatory cell milieu was altered, which could leading to cell senescence [51,62]. This speculation might explain the reason why CDK4/6 inhibitors caused lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although palbociclib is generally well tolerated, pulmonary toxicity associated with palbociclib is a rare but potentially serious adverse event. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%